Fingerprinting Global Climate Change and Forest Management Within Rhizosphere Carbon and Nutrient Cycling Processes - XU, Zhihong (Environmental science and pollution research international, 2006)
As one of the two Principal Subject Editors for ESPR Subject Area 1 'Terrestrial Ecology and Biology / Soil and Sediments: Toxicology-related Subjects' (see pp 287-293), the senior author and his colleague, Dr Chen, present an example of sub-category 4 'Environmental studies of pesticides, air pollution, and management strategies for forestry and plant ecosystems'. Thereby, they inform the ESPR community about the new Australian research project concerning the fingerprints of global climate change (GCC) and forest management on rhizosphere carbon and nutrient cycling and, subsequently, present an overview on the GCC and forest management fingerprints.